Nullane salus extra ecclesiam - P. Gautret; D. Raoult (New Microbes and New Infections, 2020)
Randomized clinical trials are not relevant for infectious disease outbreaks due to a new pathogen, for which public health decisions have to be made urgently. An approach based on group comparisons, in silico, may provide valuable results in a reasonably short period of time for a negligible amount of money.